Willingness to pay for hand, foot, and mouth disease vaccination in Ho Chi Minh City, Vietnam: A cross-sectional analysis - Tran Bao La; Trung Quang Vo; Quang Vinh Tran; Roy Rillera Marzo; Bay Van Vo; Yogambigai Rajamoorthy; Hana W. Jun Chen (Asian Pacific Journal of Tropical Medicine)
Objective: To estimate the willingness to pay (WTP) of Ho Chi Minh City residents for the hand, foot, and mouth disease (HFMD) vaccine and its associated factors using the contingent valuation method. Methods: This cross-sectional study was conducted in 2024, involved face-to-face interviews with 423 participants in Ho Chi Minh City. The participants were divided into two groups: parents of children under six and individuals without young children. WTP for the HFMD vaccine was assessed using the Krinsky and Robb procedure and the double-bound dichotomous choice technique. A probit regression model was used to analyze factors influencing WTP. Results: The participants had a mean age of (34.0±10.3) years, and the majority of them were female, resided in urban areas, and held a university degree. 54.6% had children under six years of age, and 63.8% had never heard of the EV71 vaccine. The mean WTP for two doses of the HFMD vaccine was VND 1 240 000 (USD 51.66). Parents of children under six years old had a mean WTP of USD 49.16, while individuals without young children had a mean WTP of USD 56.25. Significant factors that were positively associated with WTP included vaccine price, younger age, higher income, and greater knowledge about vaccines. Conclusions: The study indicates a relatively high willingness to pay for HFMD vaccination in Ho Chi Minh City, suggesting strong potential for vaccine implementation. It is recommended that the government disseminate vaccine-related information to enhance public awareness and understanding.